Exploration of the value of science in the selametan brokohan tradition that develops among the Banyuwangi community - Ratnawati, Dewi Mei; Wahida, Ken Ismi Zanuba; Nuris, Salsabila Faradisa; Maesaroh, Riska Findia; Hasanah, Rafiatul (ATTARBIYAH: Journal of Islamic Culture and Education, 2021)
Brokohan is a tradition of salvation that is routinely held by people on the East Java,including Banyuwangi. This tradition is carried out as an expression of gratitude for the birth of a baby in a family. The prayer used in the selametan brokohan salvation is to use Javanese and Arabic. Everyone who comes to the salametan brokohoan tradition will be given “berkat” to take home and can be enjoyed by the family. The purpose of this study was to determine the moral and scientific values that developed in a society with the brokohan tradition. The data collection used in this study was through structured interviews. The data obtained from the research were processed descriptively. Through this research, information can be obtained about the origin of salametan brokohan, the benefits obtained, and the value of knowledge. One of the ingredients used is rice, which we consume every day. In general science, it means to bring blessings and scientifically is the staple food of Indonesians.